2020
DOI: 10.3390/ijerph17249527
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Neighborhood Social Environment in Physical Activity among Hispanic Children: Moderation by Cultural Factors and Mediation by Neighborhood Norms

Abstract: Little is known about how the neighborhood social environment (e.g., safety, crime, traffic) impacts child physical activity. We examine the mechanism by which the neighborhood social environment is associated with child physical activity, moderated by individual-level cultural factors (e.g., language at home, immigrant generation) and mediated by neighborhood physical activity-related social norms (e.g., seeing walkers in the neighborhood). Data included 2749 non-Hispanic White and Hispanic children from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…49 It has been speculated that residence in a high-opportunity neighborhood may increase exposure to visual cues of other children actively using resources in the neighborhood, which may subsequently alter children's behavior and health outcomes. 49 This observation was previously found to be more impactful for Hispanic individuals compared with non-Hispanic White individuals. 50,51 Given that Hispanic children are known to be at increased risk of obesity compared with non-Hispanic White children, 52 further studies are warranted to investigate the mechanisms behind these different associations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 It has been speculated that residence in a high-opportunity neighborhood may increase exposure to visual cues of other children actively using resources in the neighborhood, which may subsequently alter children's behavior and health outcomes. 49 This observation was previously found to be more impactful for Hispanic individuals compared with non-Hispanic White individuals. 50,51 Given that Hispanic children are known to be at increased risk of obesity compared with non-Hispanic White children, 52 further studies are warranted to investigate the mechanisms behind these different associations.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of an association between exposure to neighborhood-level opportunity or vulnerability measures and larger differences in mean BMI and risk of obesity in Hispanic children is consistent with a previous study that reported Hispanic children who lived in high-opportunity neighborhoods (vs those who did not) were more physically active. 49 It has been speculated that residence in a high-opportunity neighborhood may increase exposure to visual cues of other children actively using resources in the neighborhood, which may subsequently alter children's behavior and health outcomes. 49 This observation was previously found to be more impactful for Hispanic individuals compared with non-Hispanic White individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Considering all the above, this study showed that some lifestyle habits related to the culture such as diet and alcohol, tobacco and drug consumption create an intercultural relationship context that has already been proven to affect immigrant individuals [ 8 , 11 , 32 ]. Furthermore, as we noticed in earlier studies, there are no significant differences, so it is possible to use this field for promoting equality through education.…”
Section: Discussionmentioning
confidence: 99%
“…In essence, this work is included in the line of research on integrative models; that is to say, it analyses the variables which influence the healthy lifestyles of a sample of young immigrants for guiding future works on the adaptation of methods, programmes, workshops, seminars and/or activities aimed at influencing even healthier lifestyles. These activities should be aimed at adolescents but also at their parents since their environments may also affect these dimensions [ 7 , 11 , 32 , 33 ]. Therefore, the objective of this work is to establish causal relationships between sports practice and healthy lifestyles in adolescent immigrants.…”
Section: Introductionmentioning
confidence: 99%
“…Nationally, 13.9% of Hispanic preschool children ages 2-5 are obese [3]-4 times more prevalent than non-Hispanic whites [4]. At the same time, 15% of Hispanic children with parents born in the United States and 17-23% of those with immigrant parents do not participate in any vigorous activity, compared to 9% of non-Hispanic whites [5]. Early care and education (ECE) sites are key locations for interventions that aim to prevent childhood obesity [6], particularly for those participating in nationally sponsored meal and physical activity programming [7].…”
Section: Introductionmentioning
confidence: 99%